2022
DOI: 10.3390/nano12020222
|View full text |Cite
|
Sign up to set email alerts
|

Βio-Based Epoxy/Amine Reinforced with Reduced Graphene Oxide (rGO) or GLYMO-rGO: Study of Curing Kinetics, Mechanical Properties, Lamination and Bonding Performance

Abstract: In this work, we report the synthesis and study of nanocomposites with a biobased epoxy/amine (Epilok 60-600G/Curamine 30-952) matrix reinforced with reduced graphene oxide (rGO) or functionalised with 3-glycidoxypropyltrimethoxysilane (GLYMO-rGO). These graphene related materials (GRMs) were first dispersed into a Curamine hardener using bath ultrasonication, followed by the addition of epoxy resin. Curing kinetics were studied by DSC under non-isothermal and isothermal conditions. The addition of 1.5 wt% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Compared to the neat epoxy, the composite material exhibited a 75% improvement in tensile strength and a 13% increase in tensile modulus. The study on the functionalization of GO with 3-Glycidoxypropyltrimethoxysilane [19][20][21] showed that the attachment of epoxy rings effectively reduces the tendency of aggregation and enhances the compatibility of GO with epoxy composites.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the neat epoxy, the composite material exhibited a 75% improvement in tensile strength and a 13% increase in tensile modulus. The study on the functionalization of GO with 3-Glycidoxypropyltrimethoxysilane [19][20][21] showed that the attachment of epoxy rings effectively reduces the tendency of aggregation and enhances the compatibility of GO with epoxy composites.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been extensively investigated and applied in various fields, including energy devices, drug delivery, catalysts, polymer composites, sensors, and electronic materials [ 11 , 12 , 13 , 14 ]. As a result, there is an increasing consensus that graphene is an ideal nanofiller to reinforce polymer nanocomposites, owing to its abundant availability and exceptional functional performance [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, carbon fiber reinforced polymers (CFRPs) have found extensive applications in military, aviation, sports, racing, wind power, and civil engineering due to their ultrahigh specific strength and modulus. 1 Consequently, the increased usage of CFRPs has led to a corresponding increase in waste production. If not fully recycled, Europe and Asia are estimated to accumulate 190,000 and 149,000 tons of waste CFRPs by 2050, respectively.…”
Section: Introductionmentioning
confidence: 99%